2019
DOI: 10.3390/photonics6020037
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Embedded Plasmonic Nanostructures on the Optical Absorption of Perovskite Solar Cells

Abstract: The interaction of light with plasmonic nanostructures can induce electric field intensity either around or at the surface of the nanostructures. The enhanced intensity of the electric field can increase the probability of light absorption in the active layer of solar cells. The absorption edge of perovskite solar cells (PSCs), which is almost 800 nm, can be raised to higher wavelengths with the help of plasmonic nanostructures due to their perfect photovoltaic characteristics. We placed plasmonic nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Spherical NPs are used most commonly in PSCs and are usually studied by embedding them in the perovskite layer; one example is shown in Fig. 2a 76 , 77 . Chang et al assessed the optical effects of Cu NPs embedded in a perovskite film by the transfer matrix method (TMM) and three-dimensional finite difference time domain (3D FDTD) method 78 .…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spherical NPs are used most commonly in PSCs and are usually studied by embedding them in the perovskite layer; one example is shown in Fig. 2a 76 , 77 . Chang et al assessed the optical effects of Cu NPs embedded in a perovskite film by the transfer matrix method (TMM) and three-dimensional finite difference time domain (3D FDTD) method 78 .…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
“… Schematics of plasmonic–perovskite solar cells by incorporating ( a ) Au nanoparticles (NPs). Adapted with permission 76 . Copyright 2019, MPDI.…”
Section: Plasmonic–perovskite Solar Cellsmentioning
confidence: 99%
“…[ 15 ] Additionally, the activation energy, work function, and electron affinity of Bi 2 Se 3 are 0.053, [ 14 ] 5.6, [ 16,17 ] and 5.3 eV, [ 18,19 ] respectively. In general, plasmonic materials can be used to increase the absorption of infrared frequencies in thin film PSCs [ 20 ] because the absorption of PSCs is very low in the near‐infrared region (NIR). [ 21 ] At the edges of nanoparticles, the LSPR effect is dominant, so a high electron density is available at the nanocrystal edges.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the PSC with Cu/Bi 2 Se 3 NSs show a 51.3% absorption enhancement compared to the PSC without NSs. be used to increase the absorption of infrared frequencies in thin film PSCs [20] because the absorption of PSCs is very low in the near-infrared region (NIR). [21] At the edges of nanoparticles, the LSPR effect is dominant, so a high electron density is available at the nanocrystal edges.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several methods have been proposed to improve the performance of perovskite solar cells, one of which involves the use of surface plasmons. Plasmonic effects could be employed to improve the performance of perovskite solar cells [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] by embedding nanoparticles [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] or plasmonic concentrators [ 31 , 32 , 33 , 34 , 35 ] that can increase absorption, especially near the optical band edge of the material. Previous theoretical research has shown that nanohole (NH) or nanodisk (ND) arrays embedded on gold electrodes with a thin layer of MAPbI deposited on them can significantly improve the solar cell PCE by up to ∼10%.…”
Section: Introductionmentioning
confidence: 99%